Responsive afatinib treatment in high-grade salivary gland ductal carcinoma and NSCLC with uncommon EGFR mutations: Treatment outcomes - Sivakamavalli Jeyachandran (Oral Oncology Reports)
In recent years, targeted therapies have revolutionized cancer treatment, particularly for tumors with specific genetic alterations. High-grade salivary gland ductal carcinoma and non-small cell lung cancer (NSCLC) are two distinct malignancies characterized by unique challenges but share uncommon epidermal growth factor receptor (EGFR) mutations as potential therapeutic targets. High-grade salivary gland ductal carcinoma, rare and aggressive, presents significant treatment challenges, with limited efficacy from traditional modalities. Recent genomic profiling has identified EGFR amplification in a subset of cases, suggesting targeted therapy potential. Afatinib, an irreversible EGFR inhibitor, has emerged as a promising option for high-grade salivary gland ductal carcinoma. Preclinical studies demonstrate its effectiveness in inhibiting tumor growth and inducing apoptosis in EGFR-amplified cell lines. Clinical trials confirm significant tumor responses and improved progression-free survival with afatinib treatment. Similarly, in NSCLC, uncommon EGFR mutations historically resistant to conventional inhibitors respond favorably to afatinib, as evidenced by clinical trials and real-world data. The success of afatinib in both malignancies underscores the importance of personalized medicine. Targeting specific genetic alterations with afatinib offers tailored treatment strategies, potentially improving outcomes and quality of life. Ongoing research aims to optimize afatinib use in these contexts, refining treatment protocols and maximizing therapeutic efficacy.